2022
DOI: 10.3390/ijerph19052899
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Self-Efficacy in the Relationship between Approach Motivational System and Sports Success among Elite Speed Skating Athletes and Physical Education Students

Abstract: Background: While the association between self-efficacy and sports success has been well established in previous studies, little is known regarding whether the basic approach motivation system contributes to this relationship in athletes. The study examines associations between self-reported temperamental approach disposition, self-efficacy, and predispositions to sports success in athletes. Methods: A cross-sectional study was performed between August 3 and 30 November 2020. The participants were 156 athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
(215 reference statements)
3
9
0
1
Order By: Relevance
“…Although, in some cases, these interplays could be considered not extremely strong in terms of correlation strength, p -value < 0.01 and sample power stronger than 90% suggests that the found relationships are statistically significant and could be considered robust. This finding aligns with previous research that has demonstrated the influence of SE on various aspects of performance and achievement [ 10 , 11 , 16 ]. Athletes with higher SE tend to set more ambitious goals and exhibit greater determination to persist through rigorous training regimens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although, in some cases, these interplays could be considered not extremely strong in terms of correlation strength, p -value < 0.01 and sample power stronger than 90% suggests that the found relationships are statistically significant and could be considered robust. This finding aligns with previous research that has demonstrated the influence of SE on various aspects of performance and achievement [ 10 , 11 , 16 ]. Athletes with higher SE tend to set more ambitious goals and exhibit greater determination to persist through rigorous training regimens.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, SE is emerging as a psychological skill training tool to influence an athlete’s performance [ 7 ] and sustain and ameliorate sport-specific performance over time [ 8 , 9 ]. Over the years, several studies have shown a positive correlation between SE and sport performance where, across various sporting and athletic endeavors, higher SE tends to be associated with enhanced performance outcomes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. On the other hand, Moritz et al [ 10 ] outlined the limitations and perspectives of this relationship contrary to Bandura’s idea of sport performance, referred to as an achievement that needs specific and objective (quantitative outcomes) descriptive criteria [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, individuals who believe that they are more capable of performing domain behaviors are more motivated and more likely to be interested in the task ( Blecharz et al, 2014 ). Self-efficacy and capacity beliefs also motivate decisions to initiate an action, the amount of effort athletes will invest, and how long they will persist in behaviors when difficulties appear, all aspects of motivated self-regulation ( Rogowska et al, 2022 ). The correlation between GSES and the metacognitive subscale is interpretable in that more efficacious athletes choose more adaptive practice strategies, including formulating specific goals, and self-evaluating to make attributions for learning ( Cleary and Zimmermann, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these elements can be similarly measured using corresponding single-dimension (e.g., General Self-Efficacy Scale, Schwarzer et al, 2009 ; Metacognitive-Self Scale, Brycz and Konarski, 2016 ) or multidimensional scales (e.g., Action Control Scale, Kuhl, 1994a ; Marszał-Wiśniewska, 2002 ). Although these corresponding measures are more general than sport-specific, they have been used in athlete research, in Polish (e.g., Marszał-Wiśniewska, 1998 ; Blecharz et al, 2014 ; Wilczynska et al, 2014 ; Serafin, 2021 ; Rogowska et al, 2022 ) and other populations (e.g., Raab and Johnson, 2004 ). Self-efficacy, for example, is critical to self-regulation and is understood as modulating one’s behavior to achieve goals ( Rogowska et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation